Transforming Indonesian Language Learning Through Augmented Reality-Based Kiddorami Flashcards in Elementary Schools - Rukma, Fajar Dwi; Sukartono, (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has changed the world of education, especially in learning Indonesian in Elementary Schools. This study discusses the transformation of Indonesian language learning through Augmented Reality (AR)-based Kiddorami Flashcards to improve letter recognition and vocabulary of grade 1 students at SD Negeri Ngadirejo 04. This study uses a descriptive qualitative method, with data collection through observation, interviews, and documentation. Planning begins with an analysis of student needs and preparation of technology infrastructure. Implementation is carried out through small group learning with interactive 3D visualization, which improves vocabulary understanding, letter recognition, and student participation. Supporting factors include the availability of technology and student enthusiasm, while the main obstacles are limited time and media access. The solution implemented is the use of a projector for collective AR access. The results of the study show that AR-based Kiddorami Flashcards significantly improve students' letter recognition and vocabulary, creating a more interactive, engaging, and technology-based learning experience. Increased student engagement and better understanding of the material prove that the use of AR in Indonesian language learning can bring positive transformations in teaching methods in Elementary Schools.